Development of a new mechano-chemical model in boundary lubrication. (January 2016) - Ghanbarzadeh, Ali; Wilson, Mark; Morina, Ardian; Dowson, Duncan; Neville, Anne
Abstract: A newly developed tribochemical model based on thermodynamics of interfaces and kinetics of tribochemical reactions is implemented in a contact mechanics simulation and the results are validated against experimental results. The model considers both mechanical and thermal activation of tribochemical reactions instead of former thermal activation theories. The model considers tribofilm removal and is able to capture the tribofilm behaviour during the experiment. The aim of this work is to implement tribochemistry into deterministic modelling of boundary lubrication and study the effect of tribofilms in reducing friction or wear. A new contact mechanics model considering normal and tangential forces in boundary lubrication is developed for two real rough steel surfaces. The model is developed for real tribological systems and is flexible to different laboratory experiments. Tribochemistry (e.g. tribofilm formation and removal) and also mechanical properties are considered in this model. The amount of wear is calculated using a modified Archard's wear equation accounting for local tribofilm thickness and its mechanical properties. This model can be used for monitoring the tribofilm growth on rough surfaces and also the real time surface roughness as well as changes in the λ ratio. This model enables the observation of in-situ tribofilm thickness and surface coverage and helps in better understanding the real mechanisms of wear. Highlights: A fairly efficient contact mechanics code adapted to real tribosystems was developed in MATLAB. A local tribofilm formation and removal model based on thermodynamics of interfaces was developed. A way of studying the effect of ZDDP tribofilm on reducing wear was proposed and examined in this work. Mechanical properties of the tribofilm were considered in the work.